PELANGGARAN KODEK ETIK PANITIA PEMILIHAN LUAR NEGERI DI MALAYSIA PADA PEMILU SERENTAK 2019 - Islami, Moh. Iqbal Alam (Bawaslu Provinsi Jawa Barat, 2023)
This research discusses violations of the Ethical Code of the Overseas Election Committee in Malaysia in the 2019 Simultaneous Elections. There are two problems in this study: first, what causes the occurrence of election violations in voting by postal methods in Malaysia; and second, how is the follow-up handling of these violations and what sanctions are in place for the Overseas Election Committee (PPLN) in Malaysia. This research uses a qualitative method with a case study approach through an organized plan or research procedure, from broad assumptions to detailed methods in data collection, analysis, and interpretation. The research findings reveal that two members of the Overseas Election Committee (PPLN) in Kuala Lumpur violated the voting process through the postal method, indicating a breach of the Ethics Code of the Overseas Voting Committee in Malaysia. The study reveals that a deputy ambassador in Kuala Lumpur, who was appointed as a member of PPLN, was involved in a conflict of interest. According to the DKPP decision, two former PPLN members are no longer eligible as election organizers. The research suggests that some election organizers may not be neutral in their decision-making and may attempt to manipulate vote results through the postal method.